Temperature driven texture and grain boundary engineering of electrodeposited β-Sn coatings and its effect on the coating corrosion behaviour: Five-parameter grain boundary character distribution analysis study. (15th April 2021) - Gupta, Abhay; Srivastava, Chandan
Abstract: Sn coatings were electrodeposited at four different temperatures (24 ˚C, 47 ˚C, 70 ˚C, and 80 ˚C) over mild steel. Electrochemical impedance spectroscopy revealed the highest and lowest corrosion resistance for Sn coating fabricated at 70 ˚C (Sn3 coating) and 80 ˚C, respectively. Electron backscattered diffraction technique was utilized to correlate the electrochemical properties with the coating texture. A significant increase in the low angle grain boundary fraction was noticed with an increase in the electrodeposition temperature. Five-parameter grain boundary character distribution analysis revealed that the highest fraction of (031)[01 ̅3] twin boundaries at 62.8˚/[100] misorientation and a high fraction of exposed low energy 100 planar orientations led to the highest corrosion resistance for Sn3 coating. Whereas a low fraction of (031)[01 ̅3] twin boundaries with a high fraction of exposed high energy 'near-(110)' planar orientations led to the poor corrosion resistance of Sn coating fabricated at 80 ˚C. Graphical abstracts: Image, graphical abstract